A SOCIOLINGUISTIC ANALYSIS OF TABOO WORDS IN ALPHA DOG MOVIE - M. Sofyan Al Farisi; Adi; Endang Setyo Astuti (UIBU, 2019)
This study is aimed at revealing the types and functions of taboo words uttered by the characters in Alpha dog movie. This study is under the concern of sociolinguistics, which is a branch of linguistics studying language and its functions in society. It also employed a descriptive qualitative method using the researcher and a data sheet as the research instruments. The data of this study were the words, phrases, clauses, and sentences uttered by the characters of Alpha Dog movie and were collected by note taking technique. The data then were analyzed by referential analysis technique. The data triangulations were also employed to confirm the validity of the data. This study reveals the type of taboo words uttered by the characters of Alpha dog movie can be classified into four; Epithet (EP), Profanity (PR), Vulgarity (VU), and Obscenity (OB). The functions of the words were classified into four; to draw attention to oneself (TDA), to show contempt (TSC), to be provocative (TBP) and to mock authority (TMA).